1965
DOI: 10.1159/000179416
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Variations in the Composition of Blood and Urine of Man Living in Hot Climate

Abstract: The diurnal variations in the composition of blood and urine during 24 h recumbency and the influence of 8 h of heavy physical work on the urinary excretory patterns were examined in nine young healthy subjects, permanent inhabitants of the hot region of Eilat near the Red Sea. The effects of change in posture, heat stress, light activity, aldosterone and dehydration on the midday sodium and water excretory patterns were studied on the same subjects. The diurnal rhythms exhibited during complete rest were simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1970
1970
1982
1982

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Most investigators have reported a diurnal variation in the urinary ex cretion of calcium and to a smaller extent magnesium, with a greater excretion of calcium occurring in the forenoon or midday and coinciding with, or slightly preceding the peak in sodium excretion [32,70,97,217,231], The mid day peak in calcium excretion is influenced by diet, and it was greatly reduced during fasting [97] or when food was given at four hourly intervals around the clock [141].…”
Section: Diurnal Variationmentioning
confidence: 99%
“…Most investigators have reported a diurnal variation in the urinary ex cretion of calcium and to a smaller extent magnesium, with a greater excretion of calcium occurring in the forenoon or midday and coinciding with, or slightly preceding the peak in sodium excretion [32,70,97,217,231], The mid day peak in calcium excretion is influenced by diet, and it was greatly reduced during fasting [97] or when food was given at four hourly intervals around the clock [141].…”
Section: Diurnal Variationmentioning
confidence: 99%